Effect of CAPE on Purin Catabolising Enzyme Activities in Bleomycine-Induced Lung Fibrosis - Özyurt, Hüseyin; Özyurt, Birsen; Söğüt, Sadık; Şahin, Şemsettin; Temel, İsmail; Akyol, Ömer (Fırat University, 2007)
Objectives: Pulmonary fibrosis (PF) induced by bleomycin (BLM) is one of the more common side effects encountered during cancer treatment. It has been suggested that the main responsible agent in PF is ROS which are generated also in normal metabolic conditions. In this study, we investigated the preventive or attenuating effects of caffeic acid phenethyl ester that has been demonstrated to have anti-inflammatory, cytocytatic, anticancerogenic, antiprolipherative and antioxidant effects on BLM-induced PF. Material and Methods: Thirty-six rats were divided four groups as sham, BLM, BLM+vitamin E and BLM+CAPE groups. BLM intratracheally, CAPE ve vit E intraperitoneally were administred. At day 14th, lung tissues were removed, xanthine oxidase, adenosine deaminase ve glutathione peroxidase enzymes activity were determined. Results: BLM application to the rats resulted in a significant increase in the XO and ADA activities as compared to the controls. Administration of CAPE and vit E led to the remarkable reduction of XO and ADA activities compared to the rats treated with BLM. There was a decreased in GSH-Px activity in BLM group to the control group. CAPE had a regulator effect on these parameters: the decreased in XO and ADA activities and the increased in GSH-Px activity were seen after CAPE application. Conclusion: We suggest that CAPE is more effective on the prevention of BLM-induced fibrosis via antioxidant and free radical scavenger properties than vit E at the doses used in the present study. CAPE has some attenuating effects PF affecting both oxidant and antioxidant systems as well as purin catabolisation. ©2007, Firat University, Medical Faculty

Giriş: Antikanserojen etkili bleomisinin (BLM), kanser tedavisi sırasında en sık rastlanan yan etkisinin pulmoner fibrozis (PF) olduğu bilinmektedir. Son yıllarda, PFden esas sorumlu ajanın, normal metabolik olaylarda üretilen reaktif oksijen türleri olduğu ileri sürülmektedir. Bu deneysel çalışmada, antienflamatuar, sitostatik, antikanserojen, antiproliferatif ve antioksidan etkisi olduğu bilinen CAPEnin BLMe bağlı PFdaki önleyici veya hafifletici etkilerinin araştırılması planlandı. Gereç ve Yöntem: 36 adet SpragueDawley cinsi sıçan Kontrol, BLM, BLM+ vitamin E (vit E) ve BLM+ CAPE olacak şekilde 4 gruba ayrıldı. BLM (7.5 mg/kg, tek doz) intratrakeal, CAPE ve vit E intraperitoneal olarak uygulandı. 14. günde akciğer dokuları çıkarıldı, ksantin oksidaz (XO), adenozin deaminaz (ADA) ve glutatyon peroksidaz (GSH-Px) enzim aktiviteleri çalışıldı. Bulgular: BLM uygulanan sıçanlarda, XO ve ADA enzim aktivitelerinde kontrol grubuna göre anlamlı artış vardı. CAPE ve E vit uygulanması ile bu iki enzim aktiviteleri özellikle BLM alan gruba göre anlamlı bir azalma gösterdi. Antioksidan enzim olan GSH-Px enzim aktivitesinde BLM verilen grupta kontrol grubuna göre anlamlı bir azalma vardı. CAPEnin bu parametreler üzerine düzenleyici etkileri: CAPE uygulandıktan sonra XO ve ADA enzim aktivitelerinde azalma, GSH-Px enzim aktivitesinde artma şeklindedir. Sonuç: BLMe bağlı PFin önlenmesinde antioksidan veya serbest radikal süpürücü etki olarak kullanılan dozlarda CAPE, E vit den daha etkilidir. CAPE, pürin katabolizması yanında hem oksidan hem de antioksidan sistemleri etkileyerek BLMe bağlı PF üzerinde iyileştirici etkiye sahiptir. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Bleomisin ile Olusturulan Akciğer Fibrozisinde Pürin Katabolizması Enzim Aktiviteleri Üzerine CAPEnin Etkisi